Atmospheric variability and precipitation in the Ross Sea region, Antarctica - Cohen, Lana (11694997) (2013)
Understanding how atmospheric variability in the Pacific sector of Antarctica drives precipitation is essential for understanding current and past climate changes on the West Antarctic Ice Sheet and the Ross Ice Shelf. Precipitation plays a key role in the Antarctic climate system (via mass balance of ice sheets) and is necessary for understanding past climates (via snow and ice proxies). However precipitation is difficult to measure and model and its variability in these regions is still not well understood. This thesis compiles three separate but inter-related studies which provide further understanding of the atmospheric variability of the Ross Sea region and its role in driving precipitation. Synoptic classifications over the Southern Ocean in the Pacific sector of Antarctica (50°S–Antarctic coast, 150°E–90°W) are derived from NCEP reanalysis data (1979–2011), producing a set of six synoptic types for the region. These six types describe the atmospheric variability of the Ross and Amundsen Seas region for the past 33 years and show how hemispheric scale circulation patterns such as the El Niño-Southern Oscillation and the Southern Annular Mode are reflected in local precipitation and temperature on the Ross Ice Shelf. The synoptic types also provide understanding of how different source regions and transport pathways can influence precipitation on the Ross Ice Shelf, which is important for the interpretation of climate proxies. Because of the sparseness of in-situ meteorological measurements in Antarctica, many studies (including the two described above) rely on atmospheric reanalyses data. However, assessments of reanalyses precipitation have only been done on annual and longer timescales. An assessment of the ERA-Interim and NCEP-2 reanalyses precipitation data on synoptic timescales is developed using statistical, event-based analysis of snow accumulation data from automatic weather stations around the Ross Ice Shelf. The results show that there are important differences between the two reanalyses products and that ERA-Interim represents precipitation better than NCEP-2 for this region. Stable isotopes in snow (δ¹⁸O and δD) are widely used as temperature proxies, but are also influenced by moisture history, source region conditions, and cloud micro-physical processes. Further understanding of the relative importance of these other factors is provided by modeling the isotopic composition of snow at Roosevelt Island, an ice core site on the Ross Ice Shelf. A Rayleigh fractionation model is used to determine isotope composition on sub-storm (hourly) timescales, and the results are compared to measured isotope composition. The model is able to reproduce the significant variability of measured isotopes and shows the importance of air-mass mixing and moisture trajectories on the isotopic composition of snow at Roosevelt Island. Together, these studies show how synoptic variability influences precipitation on the Ross Ice Shelf and at Roosevelt Island in particular, and they provide a basis for interpreting stable isotopes and other precipitation-based climate proxies in ice cores from the Roosevelt Island site.